Media Sosial, Eco-Anxiety, dan Penghayatan Ekologis: Perspektif Generasi Z - Ahmad Fadhli; Aldin Aldama; Madani Sri Rahayu; Nabilah Salsabila (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This research is motivated by the issue of environmental damage, with the emergence of the social media phenomenon